The Basic Safety Standard (Standar Keselamatan Radiasi) - B.Y. Eko Budi Jumpeno (Widyanuklida, 1999)
ABSTRAK Dalam kerangka kerja the Inter-Agency Committee on Radiation Safety (IACRS), telah dibentuk suatu sekretariat bersama oleh enam organisasi internasional pada tahun 1991. Beberapa anggota komite ini yaitu IAEA, ILO, OECD/NEA, FAO, PAHO dan WHO kemudian mensponsori terbentuknya the International Basic Safety Standards for Protection against Ionizing Radiation and for the Safety of Radiation Sources atau dikenal dengan the Basic Safety Standard (BSS). Setelah disetujui oleh semua organisasi sponsor, BSS diterbitkan dalam IAEA Safety Series No. 115 pada tahun 1996. Dalam tulisan ini akan diuraikan sejarah singkat standar keselamatan radiasi, pengertian tentang efek radiasi, practices dan interventions, tujuan pembentukan BSS, ruang lingkup BSS, kewajiban dalam BSS, serta persyaratan dalam pelaksanaan BSS. ABSTRACT Under an umbrella of the Inter-Agency Committee on Radiation Safetv (lACRS) and under coordinationship of the International Atomic Energy Agency, six international organizations have founded a joint-secretariate in 1991. The members of the secretariate. i.e. IAEA, ILO, OECD/NEA, FAO, PAHO and WHO then worked on to establish the International Basic Safety Standards for Protection against ionizing Radiation and .for the Safety of Radiation Sources or the Basic Safety Standard (BSS). The standard was issued as IAEA Safety Series No. 115 in 1996. This paper covers a brief discussion on radiation safety standard radiation effects, practices and interventions. It also covers a presentation on the goal and scope of the BSS and what have to be prepared for the implementation of the BSS.